AB0811 Carotid Atherosclerosis is Associated with Compromised Volumetric Bone Mineral Density and Microstructure in Patients with Psoriatic Arthritis. (9th June 2015) - Shen, J.; Shang, Q.; Li, E.K.; Zhu, T.Y.; Qin, L.; Tam, L.-S.
Abstract : Background: Considerable evidence supports a relationship between low bone mineral density (BMD) and the presence of atherosclerotic plaque in the general population, probably related to molecular pathways between bone disease and formation of atherosclerotic plaque. Patients with psoriatic arthritis (PsA) have increased risk of subclinical atherosclerosis (SCA) and osteoporosis. Whether there is any association between SCA and volumetric BMD (vBMD) and microstructure has never been explored in PsA patients. Objectives: The aim of this study is to examine the association between SCA and vBMD and bone microstructural features in PsA patients. Methods: 95 PsA patients (51 males; age: 54±11 years) were included. Carotid plaque and intima-media thickness (IMT) were measured by carotid ultrasound. vBMD and microstructural features of the distal radius were measured using high-resolution peripheral quantitative computed tomography (HR-pQCT). Results: No PsA patients had clinically overt cardiovascular diseases (CVD). Forty (42.1%) patients were found to have ≥1 carotid plaque(s). Patients with plaque were significantly older (59±11 vs 51±10 years, p =0.001), had a longer PsA disease duration (16±7 vs 13±7 years, p =0.041) and an increased prevalence of high CV risk (Framingham risk score [FRS] 10-year CVD risk >10% in 65% vs 35%, p =0.003) than patients without plaque. Patients with plaque were more likely to be male (65% vs 46%, p =0.059). Total vBMD and trabecular vBMD were 13.0% ( p =0.005) and 13.5% ( p =0.021) less in patients with plaque, respectively (Table 1 ). Bone microstructure were also inferior in patients with plaque as trabecular bone volume fraction, trabecular and cortical thickness were 13.4% ( p =0.021), 11.2% ( p =0.008) and 11.8% ( p =0.033) lower, respectively. These differences remained significant after adjustment for age, gender, PsA disease duration and FRS score (all p <0.05). Cortical vBMD and porosity were not significantly different between the two groups. Patients with plaque also had significantly lower biomechanical indices including stiffness, modulus, failure load and trabecular average stress after adjustment (all p <0.05). On the other hand, mean or maximum IMT was not associated with vBMD or microstructural features. Conclusions: PsA patients with SCA have lower vBMD, compromised bone microstructure and strength in the distal radius compared with those without SCA even after adjustment for age, gender and CVD risk factors, supporting linkage of molecular pathways between bone disease and formation of atherosclerotic plaque. Disclosure of Interest: None declared